TT Ari: Out from the Positive Superhump State - Andronov, I. L.; Burwitz, V.; Chinarova, L. L.; Gazeas, K.; Kim, Y.; Niarchos, P. G.; Ostrova, N. I.; Patkos, L.; Yoon, J. N. (Information Bulletin on Variable Stars, 2005)
The nova-like variable TT Ari had shown a luminosity change with a drastic change of the light curve. This state is distincly different from both the bright "negative superhump" state and the "positive superhump" state known before.
Keywords: Photometry